Polygraph-assessment test for pre employment of information technology personnel - Yusoff, Hashim (2001)
With the advent of information and communication technologies, the vision of perfect competition is becoming a reality. A skilled, efficient and knowledgeable labor force is a prerequisite towards achieving developed nation status. The need fix Information Technology (IT) knowledge and competent personnel in Malaysia is very great. This research study focuses on the pre employment testing using polygraph instrument on information technology (IT) personnel of Universiti Teknologi Malaysia. It also focuses on their understanding and perception on polygraph testing as a pre employment tool for hiring decision. Polygraph pre employment testing can provide additional piece of valuable information that can help to make a more accurate hiring decision. The polygraph is an investigative tool to determine the accuracy of the submitted Personnel Data Questionnaire, to uncover undisclosed misdeeds, and to reveal false statements. It has proven very effective in these tasks. Many employers like to use pre-employment tests as a way to screen out applicants who are not suitable for the job and to screen in potential employees. It bas increasingly difjicult to recruit and retain qualified workers information technology personnel but with new knowledge and skills of personnel selection process through pre employment testing, this can be met. This information can also provide a basis for accessing IT employment policy alternatives. Employers seeking persons to fill high level or skill specific positions may want to extend their screening process to include competency testing, integrity testing and polygraph test especially with the advancement of information system and information technology. This reserach explores the use of information technology tools and polygraph instrument as a tool for pre employment testing of information technology personnel assessing measurement of behavioral traits of theft propensity, illegal drug use, alcohol use, work history, work attitudes, customer service, fundamental data and credibility. It provides a database on the IT personnel tested. The study indicate that there is a sigdkant response towards understanding, perception and application of polygraph testing for pre employment.